Revision Surgery in Total Joint Replacement Is Cost-Intensive. (25th September 2018) - Weber, Markus; Renkawitz, Tobias; Voellner, Florian; Craiovan, Benjamin; Greimel, Felix; Worlicek, Michael; Grifka, Joachim; Benditz, Achim
Abstract : Revisions after total joint replacement increase constantly. In the current study, we analyzed clinical outcome, complication rates, and cost-effectiveness of revision arthroplasty. In a retrospective analysis of 162 revision hip and knee arthroplasties from our institutional joint registry responder rate, patient-reported outcome measures (EQ-5D, WOMAC), complication rates, and patient-individual charges in relation to reimbursement were compared with a matched control group of primary total joint replacements. Positive responder rate one year postoperatively was lower for revision arthroplasties with 72.9% than for primary arthroplasties with 90.1% (OR=0.30, 95%CI=0.18–0.59, p=0.001). Correspondingly, improvement in patient-reported outcome measures one year after surgery was lower in revision than in primary joint arthroplasty with EQ-5D 0.19±0.25 to 0.30±0.24 (p<0.001) and WOMAC 24.3±30.3 to 41.2±21.3 (p<0.001). Infection rate was higher in revision (6.8%) compared to primary replacements (0%, p=0.001). Mean charges in revision arthroplasty were 76.0% higher than in matched primary joint replacements (7110.8±2249.4$ to 4041.1±975.7$, p<0.001), whereas reimbursement was only 23.6% higher (9243.3±2258.4$ in revision and 7477.9±703.1$ in primary arthroplasty, p<0.001). Revision arthroplasty is associated with lower outcome and higher infection rate compared to primary replacements. The high financial expense of revision arthroplasty is only partly covered by a higher reimbursement.